Autologous Stem Cell Transplantation for Myeloma: Cytoreduction or an Immunotherapy? - Minnie, Simone A.; Hill, Geoffrey R. (Frontiers in Immunology, 2021)
The incidence of multiple myeloma (MM), a bone marrow (BM) resident hematological malignancy, is increasing globally. The disease has substantial morbidity and mortality and remains largely incurable. Clinical studies show that autologous stem cell transplantation (ASCT) remains efficacious in eligible patients, providing a progression free survival (PFS) benefit beyond novel therapies alone. Conventionally, improved PFS after ASCT is attributed to cytoreduction from myeloablative chemotherapy. However, ASCT results in immune effects beyond cytoreduction, including inflammation, lymphodepletion, T cell priming via immunogenic cell death, and disruption of the tumor BM microenvironment. In fact, a small subset of patients achieve very long-term control of disease post-ASCT, akin to that seen in the context of immune-mediated graft-versus-myeloma effects after allogeneic SCT. These clinical observations coupled with recent definitive studies in mice demonstrating that progression after ASCT represents immune escape as a consequence of T cell exhaustion, highlight the potential for new immunotherapy maintenance strategies to prevent myeloma progression following consolidation with ASCT.